US authorities recover most of Colonial Pipeline ransom. Issue 6 (June 2021) - Unknown
Abstract : Shortly after the creation of a new Ransomware and Digital Extortion Task Force, the US Department of Justice (DOJ) announced that it had recovered most of the ransom payment made by Colonial Pipeline – although questions remain over how it managed to do that.